Relevance of congenital melanocytic naevi in vitiligo. (1st April 2015) - van Geel, N.; Van Poucke, L.; Van de Maele, B.; Speeckaert, R.
Summary: Background: Some case reports concerning the concomitant presence of congenital melanocytic naevi (CMN), halo naevi and vitiligo have been published. However, their possible link has never been investigated in a large patient population. Objectives: To evaluate the relevance of CMN in patients with vitiligo with respect to the presence of halo naevi and some general clinical variables such as age of onset, Koebner phenomenon and body surface area (BSA) involvement. Methods: In total, 1004 patients with vitiligo (nonsegmental) and 291 control patients were included in this observational study. CMN were scored in size, location and halo formation, and classified into clinical convincing or possible lesions. Results: Convincing CMN were present in 3·3% of the patient population and in 1·0% of the control population. The presence of halo naevi was significantly higher ( P = 0·01) and age of onset of vitiligo was significantly lower ( P < 0·01) in the presence of CMN. Halo formation around the CMN, as observed in 30·3% of cases, was associated with a higher diameter of the CMN. Patients with congenital naevi had a particular predisposition to having lesions on joints/acral areas and reported more often signs of Koebner phenomenon ( P = 0·01). No clear difference in disease activity, BSA involvement, associated autoimmune diseases or treatment response was observed in patients with vitiligo with or without congenital naevi. Conclusions: This study provides clinical evidence that CMN may influence the age of onset of vitiligo and trigger the development of halo naevi in patients with vitiligo.